Service life evaluation of ballastless track construction - S. V. Mikhaylov (Вестник Научно-исследовательского института железнодорожного транспорта)
The article presents method for calculating service life of ballastless track structure using the track oscillation model as a structure containing three infinitely long beams, the lower of which lies on the modified Winkler base, and the upper and middle are based on elastic layers, mainly having the characteristics of Winkler. The use of this model is due to the need to carry out calculation for bearing concrete slab, the destruction of which is the main reason for the failure of the ballastless track structure. First part of the article presents model for calculating service life of a ballastless structure. When calculating the damage index, which takes the stresses in the bearing concrete slab, to estimate the vertical dynamic forces acting on the track, it is proposed to use a frequency response that determines the dynamic system with input on the track unevenness and output on the dynamic force at the wheel and rail contact in the model oscillations of the track as a three-layer beam. Second part presents estimates of the service life of ballastless structure for various operating conditions and their comparison with the results obtained using the practice method with the single-beam model. Graphs were plotted for the service life of the ballastless track structure on axle loads, the speed of the carriages and the load capacity on the line. Results show the applicability of the single-layer beam model for estimating the service life of the ballastless track structure in the current operating conditions; however, for the promising conditions of high-speed and heavy traffic, it is advisable to use a three-layer model.